2005
DOI: 10.1021/ic051491x
|View full text |Cite
|
Sign up to set email alerts
|

Large Gas−Solid Structural Differences in Complexes of Haloacetonitriles with Boron Trifluoride

Abstract: The structural properties of the singly halogenated derivatives of CH(3)CN-BF(3) (X-CH(2)CN-BF(3): X = F, Cl, Br, I) have been investigated via single-crystal X-ray crystallography, solid-state infrared spectroscopy, and correlated electronic-structure theory. Taken together, these data illustrate large differences between the gas-phase and solid-state structures of these systems. Calculated gas-phase structures (B3PW91/aug-cc-pVTZ) of FCH(2)CN-BF(3), ClCH(2)CN-BF(3), and BrCH(2)CN-BF(3) indicate that the B-N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 30 publications
3
45
0
Order By: Relevance
“…The latter explanations on the boron acidity for BH 3 and boron trihalides are in line with recent calculations for the BF 3 -NCH [9] and BH 3 -NCH [10] complexes in which stronger Lewis acid properties of BH 3 were observed, because the binding energy for the latter complex is À19.9 kcal mol À1 , whereas for the former complex it is À6.3 kcal mol À1 [MP2/aug-cc-pVTZ level, basis set superposition error (BSSE) correction not included]. [12,13] The importance of the frontier orbital interactions in small complexes such as BH 3 -NH 3 and BH 3 -CO was analyzed earlier. [11] Other complexes of boron trihalides and BH 3 were also analyzed both theoretically and experimentally.…”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations
“…The latter explanations on the boron acidity for BH 3 and boron trihalides are in line with recent calculations for the BF 3 -NCH [9] and BH 3 -NCH [10] complexes in which stronger Lewis acid properties of BH 3 were observed, because the binding energy for the latter complex is À19.9 kcal mol À1 , whereas for the former complex it is À6.3 kcal mol À1 [MP2/aug-cc-pVTZ level, basis set superposition error (BSSE) correction not included]. [12,13] The importance of the frontier orbital interactions in small complexes such as BH 3 -NH 3 and BH 3 -CO was analyzed earlier. [11] Other complexes of boron trihalides and BH 3 were also analyzed both theoretically and experimentally.…”
Section: Introductionsupporting
confidence: 85%
“…[14,15] The interaction of the sp 2 -hybridized boron center with Lewis bases often leads to rehybridization of the boron center, as the Lewis base disrupts the p bond in the B trigonal reactant and leads to sp 3 hybridization of the product. [13] The hydridic character of the hydrogen atoms of the ÀBH 3 group attached to the Lewis base centers, that is, at which the boron is tetravalent, was analyzed recently in numerous structures. For example, amine systems, such as the MP2/aug-cc-pVTZ calculations were performed on triel trifluorides, ZF 3 (Z = B, Al, Ga, In, Tl), and their complexes with N 2 and HCN species, which are acting as Lewis bases.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Equilibrium geometries were obtained within the C3v point group, and all gas-phase optimizations were performed using the "opt=tight" option with an "ultrafine" integration grid, while standard convergence criteria were employed for optimizations in dielectric media. Seeking a prediction of the gas-phase H-Cl stretching frequency for CH3CN-HCl, we initially attempted a validation study based on the prediction of the frequency of free HCl, akin to our previous studies of Lewis acid-base systems [30,31]. In this process, we explored the performance of 18 different density functionals as well as MP2, and found that anharmonic frequency predictions were essential to obtain any reasonable agreement with the experimental frequency [32].…”
Section: Computationsmentioning
confidence: 99%